2004
DOI: 10.1152/ajprenal.00338.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression and relative abundance of short transient receptor potential channels in the rat renal microcirculation

Abstract: Facemire, Carie S., Peter J. Mohler, and William J. Arendshorst. Expression and relative abundance of short transient receptor potential channels in the rat renal microcirculation. Am J Physiol Renal Physiol 286: F546-F551, 2004. First published December 16, 2004; 10.1152/ajprenal.00338.2003In the resistance vessels of the renal microcirculation, store-and/or receptor-operated calcium entry contribute to the rise in vascular smooth muscle cell (VSMC) intracellular calcium concentration in response to vasocons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 39 publications
6
70
1
1
Order By: Relevance
“…TRPC4 has four protein variants, with the full-length species containing 974 amino acids and a predicted molecular mass of ϳ112 kDa. The protein species we observed is likely to be a variant that contains 564 amino acids and has been reported previously (19). The anti-TRPV1 antibody weakly detected a protein species of 75 kDa, and this binding was abolished by the control peptide (Fig.…”
Section: Western Blot Analysis Confirms Expression Of Trp Channels Insupporting
confidence: 85%
“…TRPC4 has four protein variants, with the full-length species containing 974 amino acids and a predicted molecular mass of ϳ112 kDa. The protein species we observed is likely to be a variant that contains 564 amino acids and has been reported previously (19). The anti-TRPV1 antibody weakly detected a protein species of 75 kDa, and this binding was abolished by the control peptide (Fig.…”
Section: Western Blot Analysis Confirms Expression Of Trp Channels Insupporting
confidence: 85%
“…TRPC1, TRPC3, TRPC4, TRPC5, and TRPC6 proteins were identified in GMCs (Facemire et al 2004;Sours-Brothers et al 2009). Previous studies demonstrated that TRPC1, 4, and 6 contributed to SOCE in GMCs (Sours-Brothers et al 2009;Wang et al 2004Wang et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Few other studies reported the presence of TRPC channels in normal rat kidney cell lines 46,47 and identified their localization in the adult rat and human kidney. [48][49][50][51] TRPC3 is also responsible for transepithelial Ca 2+ flux in principal cells of the renal collecting duct [52][53][54] ; however, a clear functional in vivo role of such channels remains totally unclear, especially in the diseased kidney. Therefore, it is important to study the role of TRPC3 in renal fibroblasts and its role in the pathogenesis of renal fibrosis associated with kidney disease.…”
mentioning
confidence: 99%